New Determination of Prey and Parasite Species for Northern Indian Ocean Blue Whales - de Vos, Asha; Faux, Cassandra E.; Marthick, James; Dickinson, Joanne; Jarman, Simon N. (Frontiers in Marine Science, 2018)
Blue whales are little studied, face significant anthropogenic threats and within the Northern Indian Ocean, have a restricted range, making them an archetype for conservation needs of megafauna around the world. We studied feeding behaviour of blue whales using dietary DNA metabarcoding of faecal samples. While globally blue whale populations feed predominantly on Euphausiidae, 87 % of prey DNA amplicons extracted from faecal samples from this population were sergestid shrimp, demonstrating that blue whales can locate and feed on dense swarms of other types of prey when they occur. Within the Indian Ocean sergestids are present within the top 300 m, which correlates with the deep scattering layer observed by hydroacoustics. Studies suggest that this requirement to dive deeper in search of prey likely explains the prevalence of fluke up diving within this population of blue whales relative to other parts of the globe. Furthermore, this study revealed the presence of acanthocephalan endoparasites within the stomach and intestines of the Northern Indian Ocean blue whales. This represents the first record of Acanthocephala in blue whales in the Northern Indian Ocean and highlights the need for further studies on both the ecto- and endoparasitic flora and monitoring of health of these cetaceans for their management and conservation.